Pemanfaatan Metode Conjoint Analysis untuk Peningkatan Rancangan Layanan Berbasis Sistem Aplikasi - Vanya Louisa; Dyah Lestari Widaningrum (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2018)
The development of information technology is very rapid. This has caused many business processes in the industry to change. One of them is in the service industry that has synergy of information technology. Provision of services is currently being developed with many application systems. It is thus important for application technology companies to define, design and realize their applications as the company's products. This research was conducted to examine the use of the Conjoint Analysis method in the application system based service industry. The assessment was conducted based on the results of research on the provision of online health services. In this study, the consumer perceptions of the service products provided by the company were examined, to determine the important factors of the design of services provided, as well as the design that became consumer preferences.